The Losting Fountain - Senf, Lora (New York : Union Square & Co., 2024)
Told in alternating voices, three teens from different time periods are called to the world of the Fountain to restore balance and prevent its eldritch creatures from seeping into the real world
Keywords: Senf, Lora; Fantasy; Fountains -- Fiction; Horror stories; Imaginary creatures -- Fiction